Comparison of Short-term Outcomes After Laparoscopic Versus Open Hartmann Reversal: A Case-matched Study. Issue 4 (August 2016) - Onder, Akin; Gorgun, Emre; Costedio, Meagan; Kessler, Hermann; Stocchi, Luca; Benlice, Cigdem; Remzi, Feza
Abstract : Purpose: The aim of this study is to compare short-term outcomes of laparoscopic versus open Hartmann reversal. Materials and Methods: Patients who underwent Hartmann reversal between January 2005 and September 2014 were identified and matched for age, sex, body mass index, American Society of Anesthesiologists score, and creation of diverting ileostomy to open counterparts. Patient characteristics and postoperative outcomes (30 d) were evaluated. Results: Eighteen patients with laparoscopic Hartmann reversal were matched to 18 open patients. There were no differences between laparoscopic versus open groups in terms of operative time (157.7±52.2 vs. 151.5±49.3 min, P >0.05) or overall complication rates [6 (33.3%) vs. 6 (33.3%) ( P >0.05)]. No anastomotic leaks or mortality occurred in either group. However, the laparoscopic group was associated with significantly decreased estimated blood loss (114±103 vs. 217±125 mL, P <0.05), faster return of bowel function (3.2±0.6 vs. 4±0.6 d, P <0.05), and reduced hospital stay (5.4±3.1 vs. 8.3±4.8 d, P <0.05). Conclusions: Laparoscopic Hartmann reversal can be safely performed with better short-term outcomes in carefully selected patients.